Deteksi Gen DXS dan Penentuan Jalur Biosintesis Karotenoid pada Chlorella pyrenoidosa - Monalita, Ramadhebi; Kusumaningrum, Hermin Pancasakti; Budiharjo, Anto (Berkala Bioteknologi, 2022)
Natural carotenoid synthesis has never exceeded synthetic products on a commercial scale. Lack of understanding of the microbiological and ecophysiological aspects of carotenoid-producing isolates leads to misidentification of species. One local isolate of green algae is used as a natural food source of carotenoids in the food industry, namely Chlorella pyrenoidosa. Carotenoid accumulation of the nonMVA pathway in green algae is determined by the enzyme D-1-deoxyxylulose 5-phosphate synthase, which is encoded by the D-1-deoxyxylulose 5-phosphate synthase (DXS) gene. The main purpose of this study was to detect the DXS gene as a carotenoid biosynthetic key enzyme encoder in C. pyrenoidosa whether or not to follow the non-MVA pathway for carotenoid biosynthesis or not. Morphological and ecophysiological characterization methods are carried out based on periodic observations and DXS gene detection using the guide Kuzuyama (2000). The results of the analysis of the similarity of the C. pyrenoidosa DXS gene in sustainable areas show that it can detect partial DXS genes from Chlamydomonas reinhardtii. The absence of growth inhibition in C. pyrenoidosa with lovastatin shows a non-MVA pathway that is the pathway used in carotenoid biosynthesis.